Relationship between single digit addition strategies and working memory reflects general reasoning sophistication. (April 2016) - Paul, Jacob M.; Reeve, Robert A.
Abstract: With age, children employ increasingly more sophisticated strategies to solve single-digit addition (SDA) number fact problems. Changes in SDA strategy-use are correlated with age-related changes in cognitive measures (e.g., working-memory capacity, WM); however, this correlation does not explain the basis of SDA strategy-use or change per se. Does strategy-use reflect differences in generally reasoning abilities or are they uniquely tied to SDA abilities? Answers to these questions would help clarify the nature of SDA abilities specifically and early math abilities more generally. To investigate these issues, we assessed 144 5- to 9-year-olds' SDA strategies, visuospatial working memory (VSWM), verbal WM, non-verbal IQ, basic RT, and visuospatial reasoning abilities. We focused on these abilities since recent research shows visuospatial processes support early math development. We used latent profile/class analysis to classify children's SDA strategies and visuospatial reasoning abilities, which yielded four ability subgroups in both cases, only partially related to age. Findings show SDA strategy subgroup and general reasoning subgroup memberships were related. More sophisticated subgroups had better WM, but did not differ in IQ and RT. Findings suggest SDA reasoning reflect general reasoning abilities. Implications for math skills acquisition and intervention are discussed. Highlights: 5- to 9-year-olds completed single digit addition and maze problem solving tasks. Latent class analyses revealed distinct SDA strategy and maze reasoning subgroups. Sophisticated subgroups had better working memory, and utilized error feedback. Overlap between subgroups ordered by sophistication, only partially related to age. Indicates general reasoning abilities are relevant for SDA strategy instruction.